2018
DOI: 10.29249/selcuksbmyd.448302
|View full text |Cite
|
Sign up to set email alerts
|

Tüketicilerin Otomobil Satın Alma Davranışlarına Etki Eden Faktörlerin Belirlenmesi: Akademisyenlere Yönelik Bir Uygulama

Abstract: Among the issues that businesses emphasized with precisely are synchronized harmony between the marketing with close and distant stakeholders of marketing. The customer, who is crucial to the survival of the enterprise, is at the forefront of these stakeholders. In this respect, the purpose of this study, which is investigate the factors affecting consumer behavior, to examine the factors affecting the buying behavior of academicians. In addition to meeting the basic needs of people such as transportation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Eight authors in the country have formed a well-structured network based mainly on two different fields, as can be seen in Figure 2. While the blue nodes deal with the purchasing behavior of current and potential EV consumers (Köylüoğlu et al, 2018a, 2018b; Yeniçeri & Güner, 2013; Yeniçeri et al, 2009), the red area includes studies on consumer assessments, changes in preferences, intentions, and motivations for EVs (Akal et al, 2019; Kiliç, 2019; Kocagöz & İğde, 2022; Kocagöz et al, 2020). Although it is observed that studies in both areas create similar common citation networks, it can be stated that there is a tendency toward the factors that motivate EV consumers and their preferences in Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Eight authors in the country have formed a well-structured network based mainly on two different fields, as can be seen in Figure 2. While the blue nodes deal with the purchasing behavior of current and potential EV consumers (Köylüoğlu et al, 2018a, 2018b; Yeniçeri & Güner, 2013; Yeniçeri et al, 2009), the red area includes studies on consumer assessments, changes in preferences, intentions, and motivations for EVs (Akal et al, 2019; Kiliç, 2019; Kocagöz & İğde, 2022; Kocagöz et al, 2020). Although it is observed that studies in both areas create similar common citation networks, it can be stated that there is a tendency toward the factors that motivate EV consumers and their preferences in Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Another result is monthly income, which is the most effective demographic factors affecting purchasing preferences, and age and gender are among other influential factors. Köylüoğlu et al (2018) tried to determine the factors affecting academicians' car buying behavior in their study in Turkey. The data collected by the survey method were analyzed by SPSS.…”
Section: "Journal Of the Human And Social Sciences Researches"mentioning
confidence: 99%